TEVFIK FIKRET’S POETICS THROUGH HIS POEMS - Bedirhan ÜNLÜ (Fırat University, 2019)
Having been used since the Ancient Greece and covering all kinds of opinions, ideas and theories about poetry, The Poetics (Poetika) reflects the poetical universe of poets. The concept of poetics, which is present in the history of Turkish literature since the collection of biographies and some prefaces, begins to be used in the modern sense after the declaration of the Republic. However, since the Tanzimat era, the period in which many Western ideas influenced the Turkish society, this way of thinking begins to be observed in poetics as well. Among the first and second period poets of the Tanzimat, Namik Kemal, Ziya Paşa, Hamit and Ekrem reflect their views on poetry to some of their prose works and poetry. Following the Tanzimat generation, the two leading poets of Servet-i Fünun period, Cenap Şehabettin and Tevfik Fikret have brought new expansions to the modern Turkish poetry with their poems as well as some writings about poetry. Tevfik Fikret, one of the leading representatives of the Servet-i Fünûn community, reveals his poetics not only in his prose works but also poems. Fikret begins to unveil his views about poetry through his poems from the first years of his art life. The title that stands out in the poems where Fikret reflects his poetics is the understanding of poet. The influence of Recaizade Mahmut Ekrem and the French Romantic and Parnassian poets is evident in the poetics of Fikret, who is trying to reflect his poetic views in his poems through his identity as a poet. Fikret engages in disclosing his views about poetry and poet in many of his works, since the first year of his career as a poet, through elements such as imagination, labor, women and music. This study examines the poetical views reflected in Tevfik Fikret's poetry by focusing on his works in this respect. Within this context, the poetics of Fikret, personally reflected through his poetry, has been examined under the headings of imagination, labor, women and music.